New Iterative Method for Solving a Coupled System of Fractional-Order Drinfeld–Sokolov–Wilson (FDSW) and Fractional Shallow Water (FSW) Equations. (7th April 2022) - Ali, Nasir; Yassen, Mansour F.; Asiri, Saeed Ahmed; Nawaz, Rashid; Zada, Laiq; Alam, Mohammad Mahtab; Sene, Ndolane
Abstract : In this study, the new iterative method has been applied to a coupled system of fractional-order Drinfeld–Sokolov–Wilson (FDSW) and fractional shallow water (FSW) equations. The fractional-order derivatives are taken in the Caputo sense whose order is between 0 and 1. The suggested method is capable to handle the FDEs without any transformation and discretization. The obtained results have been compared with the exact solution and with the q-homotopy analysis transform method. The outcomes show the efficiency and effectiveness of NIM by comparing through tables and graphs.